Antimicrobial never events: Objective application of a framework to assess vancomycin appropriateness. (29th September 2021) - Liu, Jiajun; Mercuro, Nicholas J.; Davis, Susan L.; Palmo, Tenzin; Kashyap, Shivek; Patel, Twisha S.; Petty, Lindsay A.; Yarnold, Paul R.; Kaye, Keith S.; Scheetz, Marc H.
Abstract: To address appropriateness of antibiotic use, we implemented an electronic framework to evaluate antibiotic "never events" (NEs) at 2 medical centers. Patient-level vancomycin administration records were classified as NEs or non-NEs. The objective framework allowed capture of true-positive vancomycin NEs in one-third of patients identified by the electronic strategy.